2020
DOI: 10.31219/osf.io/rjmfq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heuristic Projection

Abstract: Can voters who know little about their representatives’ actions effectively hold them accountable? An influential perspective argues that voters can infer their representatives’ actions by using interest group ratings as heuristics. Across nine studies in four original samples, we show that information about interest group ratings can have surprisingly pathological effects on voters’ judgments about their representatives. In our studies, voters shown interest group ratings are typically no more accurate at inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recall that the retracted LaCour-Green study was pre-registered, yet evidence of fraud was uncovered not by comparing the published article to the pre-registration plan, but by scrutinizing the article and accompanying dataset. 51 The only viable strategy in our view involves disciplinary norms. First, we need a commitment to truth-seeking and scientific integrity.…”
Section: Integritymentioning
confidence: 98%
“…Recall that the retracted LaCour-Green study was pre-registered, yet evidence of fraud was uncovered not by comparing the published article to the pre-registration plan, but by scrutinizing the article and accompanying dataset. 51 The only viable strategy in our view involves disciplinary norms. First, we need a commitment to truth-seeking and scientific integrity.…”
Section: Integritymentioning
confidence: 98%
“…How does this informational cue perform compared to the party identification heuristic? Broockman et al [11] interrogate this question using a series of nine experiments across four original survey samples, finding that a positive endorsement, regardless of its source, increases respondents' approval of their representative, and increases their perception of ideological similarity with that representative.…”
Section: Testing the Interest Group Endorsement Heuristic With Respondentadaptive Questionsmentioning
confidence: 99%
“…Across several policy areas, researchers have found liberals prefer contemporary policies far more than even the older policies that liberal politicians supported, as civil rights, immigration, and gay rights policies have all moved leftward over time. 73 Despite this backdrop of increasing worldwide government growth and social change, there is a very large academic literature (concentrated in studies of Europe) about the extent to which party power and ideological conflict determine the levels of policy liberalism across nations. A review of 100 studies that look at changes over time in policy across rich countries found that left and right governments pursued different economic policies until the 1990s, with size and scope of government larger under left governments.…”
Section: Learning From Conservative Difficulties Worldwidementioning
confidence: 99%